EMI in Vietnam: What High School Teachers Think and Do - Thi Phuong Doan Nguyen; Van Loi Nguyen (Universitas Jambi, Magister Program of English Education Department, 2020)
The current case study was driven by a recent policy on using English as a medium of instruction (EMI) in the mainstream school system in Vietnam. It aimed to explore what science teachers believed and reported doing about EMI in teaching science subjects in the high school context. Nine EMI teachers of different science subjects at a specialized high school in the Mekong Delta of Vietnam participated in a semi-structured interview. Thematic analysis revealed the perceived positive impacts on teachers’ and students’ English proficiency, and negative influences on science content coverage. In practice, the teachers reported a focus on simple contents, explaining specialized terminologies and key concepts as the input. They mainly employed a lecture style and teacher initiation-student response interaction, switching between English and Vietnamese during their lessons. These results imply that EMI across the curriculum has the potential to improve English proficiency of students, but the EMI policy needs to consider its transparency in goals and communication to stakeholders especially teachers and school managers.